The image of Nicholas I in sources of personal origin: Russian-Polish discourse - N. A. Cherkasskaya (Омский научный вестник: Серия "Общество. История. Современность")
Currently, one of the topical issues for Russian historians is the study of the personalities of Russian monarchs including tsars and emperors of the Romanov dynasty. The problem of constructing the image of a representative of power both in Russia and abroad especially in the light of the problems of nation-building also relevant among researchers is revealed. The purpose of our work is to reconstruct the images of emperor Nicholas I to reveal their transformation, similarities and differences within the framework of the Polish question. The article analyzes Russian and Polish sources of personal origin in the 1820s–1830s in the context of the Polish coronation of 1829 and the uprising of 1830–1831. Using historical and anthropological approach they have the opportunity to identify the features of the formation of emperor’s image. The historical-comparative method let us to analyze the characteristics that the emperor was endowed with by his contemporaries and to reconstruct the chronological evolution of the images of Nicholas I. The main result of this evolution can be called the moment of separation of the image of the Russian emperor from the image of the polish king, which was repeatedly emphasized by both Russian and Polish contemporaries, and by the emperor himself. The selfidentification of Nicholas I as the Russian autocratic monarch was one of the results of the Polish uprising of 1830–1831 that followed soon after the coronation